José Jiménez Lozano: The Coincidence within Fiction (XXI Century. Spanish Literature and Culture, 2003)
A study on José Jiménez Lozano’s writing, winner of the Miguel de Cervantes Prize, who has a wide literary production in almost all literary genres. In some of his works we can see the current political atmosphere, even when almost all of his work is of a historic or philosophical nature.
Keywords: Jiménez Lozano; Narrative; Novel; Essay; Transition